Determinants, Costs, and Consequences of Common Bile Duct Injury Requiring Operative Repair Among Privately Insured Individuals in the United States, 2003–2020 - Holly Elser, MD, PhD; John R. Bergquist, MD; Amy Y. Li, MD; Brendan C. Visser, MD (Annals of Surgery Open, 2023)
Objective:. Characterize the determinants, all-cause mortality risk, and healthcare costs associated with common bile duct injury (CBDI) following cholecystectomy in a contemporary patient population. Background:. Retrospective cohort study using nationwide patient-level commercial and Medicare Advantage claims data, 2003–2019. Beneficiaries ≥18 years who underwent cholecystectomy were identified using Current Procedure Terminology (CPT) codes. CBDI was defined by a second surgical procedure for repair within one year of cholecystectomy. Methods:. We estimated the association of common surgical indications and comorbidities with risk of CBDI using logistic regression; the association between CBDI and all-cause mortality using Cox proportional hazards regression; and calculated average healthcare costs associated with CBDI repair. Results:. Among 769,782 individuals with cholecystectomy, we identified 894 with CBDI (0.1%). CBDI was inversely associated with biliary colic (odds ratio [OR] = 0.82; 95% confidence interval [CI]: 0.71–0.94) and obesity (OR = 0.70, 95% CI: 0.59–0.84), but positively associated with pancreas disease (OR = 2.16, 95% CI: 1.92–2.43) and chronic liver disease (OR = 1.25, 95% CI: 1.05–1.49). In fully adjusted Cox models, CBDI was associated with increased all-cause mortality risk (hazard ratio = 1.57, 95% CI: 1.38–1.79). The same-day CBDI repair was associated with the lowest mean overall costs, with the highest mean overall costs for repair within 1 to 3 months. Conclusions:. In this retrospective cohort study, calculated rates of CBDI are substantially lower than in prior large studies, perhaps reflecting quality-improvement initiatives over the past two decades. Yet, CBDI remains associated with increased all-cause mortality risks and significant healthcare costs. Patient-level characteristics may be important determinants of CBDI and warrant ongoing examination in future research.